Classification of sliding formwork systems - Halenko, Y.; Makhynia, O. (Ways to Improve Construction Efficiency, 2023)
The article discusses modern sliding formwork systems, which are different from other types of formworks in that they can be moved during the construction of structures without the need for intermediate stages of formwork installation and removal. This, and the possibility of using a high level of process automation, allows to increase the rate of monolithic construction and significantly reduce the number of working seams, which in turn increases the structural reliability and reduces the complexity of formwork operations. The development of constructive solutions for sliding formwork systems has created a significant range of varieties of these systems, which allows expanding the range of applications for sliding formwork. Based on the analysis of existing sliding formwork systems, their classification is proposed according to the factors that influence the constructive solutions, namely: constructive solutions of forming elements, constructive solutions of the supporting part of the formwork system and the mechanism of movement of the formwork system in the process of constructing a monolithic structure. It is proposed to classify sliding formwork systems according to the following features of the structural solutions of the forming elements, namely: the size of the formwork panels; the shape of the surface of the forming elements; the location of the forming elements in relation to the structure being constructed; the geometry of the forming elements; the method of fixing the forming elements in relation to the surface of the structure being constructed; the material of the surface of the forming elements in contact with the freshly placed concrete mixture. According to the constructive solutions of the supporting part of the formwork system, it is proposed to consider the following features: the method of supporting the formwork part; the construction of jacking frames; the location of jacking rods. According to the mechanism of movement of the supporting part of the formwork system, it is proposed to distinguish the following features: elements that move in the process of raising a monolithic structure; direction of movement of the sliding formwork system; types of jacks used to move the formwork system; control system for moving the sliding formwork system. The presented classification takes into account technical parameters and functional properties, which contributes to a better understanding of the choice of the best type of formwork for specific construction tasks. The results of the study may be useful for engineers, architects and other construction industry professionals interested in improving the efficiency and quality of construction projects.